2005
DOI: 10.1002/eji.200526218
|View full text |Cite
|
Sign up to set email alerts
|

Transient T cell accumulation in lymph nodes and sustained lymphopenia in mice treated with FTY720

Abstract: hydrochloride) is an orally available immunomodulatory agent that induces severe peripheral blood lymphopenia. Most studies of these lymphopenic effects have been limited to short-term exposure to FTY720. FTY720 alters the ability of lymphocytes to respond to sphingosine-1-phosphate (S1P) through S1P receptors, particularly S1P 1 . FTY720 affects different leukocyte populations and their trafficking through major lymphoid organs. We show the dynamics of CD4 T, CD8 T, and B lymphocyte recirculation in all major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 30 publications
11
72
0
Order By: Relevance
“…3), these effects appear to impact upon DCs recruited to tissues p.i. In experiments involving FTY720 treatment during established infection, we also observed decreased mononuclear cell numbers in the liver and spleen (data not shown), consistent with previous reports showing that long-term drug treatment results in decreased lymphocyte numbers in the body (53). Thus, we were unable to assess the requirements for tissue migration of CD4 + T cells on the maintenance of antiparasitic immunity in infected organs.…”
Section: Discussionsupporting
confidence: 88%
“…3), these effects appear to impact upon DCs recruited to tissues p.i. In experiments involving FTY720 treatment during established infection, we also observed decreased mononuclear cell numbers in the liver and spleen (data not shown), consistent with previous reports showing that long-term drug treatment results in decreased lymphocyte numbers in the body (53). Thus, we were unable to assess the requirements for tissue migration of CD4 + T cells on the maintenance of antiparasitic immunity in infected organs.…”
Section: Discussionsupporting
confidence: 88%
“…FTY720 administration causes transient sequestration of circulating lymphocytes in lymph nodes and a sustained decrease of lymphocytes in the blood and spleen (13,14,(36)(37)(38). Consistent with other studies (38), we observed a marked reduction of lymphocytes in the blood (data not shown).…”
Section: Fty720 Treatment Of Ecm Decreases Central Nervous System Lymsupporting
confidence: 92%
“…During FTY720 and LX2931 treatment, oral rather than intravenous administration was preferred since it has been shown that lower blood lymphocyte counts can be achieved using this route (38). Dosing was based on the preestablished range shown to reduce lymphocyte numbers in the blood (15).…”
Section: Genetic Approaches Using Hs1plmentioning
confidence: 99%
“…Although it is considered that FTY720 is a prodrug that is active only after phosphorylation, it should be noted that plasma concentrations not only of FTY720-P but also of FTY720 reach steadystate levels of 30 nM, both in humans and in experimental animal models. [61][62][63] This is within the range of concentrations that significantly inhibit cPLA 2 . Of importance, the half-life for clearance of FTY720 in humans is nearly 8 days, 61 and we observed that nanomolar concentrations of FTY720 markedly inhibited eicosanoid release from mast cells and macrophages within a very short period of treatment (15 minutes to 2 hours).…”
Section: Discussionmentioning
confidence: 53%